CAMP-Protein kinase A and stress-activated MAP kinase signaling mediate transcriptional control of autophagy in fission yeast during glucose limitation or starvation. Issue 4 (3rd April 2023) - Pérez-Díaz, Armando Jesús; Vázquez-Marín, Beatriz; Vicente-Soler, Jero; Prieto-Ruiz, Francisco; Soto, Teresa; Franco, Alejandro; Cansado, José; Madrid, Marisa
ABSTRACT: Macroautophagy/autophagy is an essential adaptive physiological response in eukaryotes induced during nutrient starvation, including glucose, the primary immediate carbon and energy source for most cells. Although the molecular mechanisms that induce autophagy during glucose starvation have been extensively explored in the budding yeast Saccharomyces cerevisiae, little is known about how this coping response is regulated in the evolutionary distant fission yeast Schizosaccharomyces pombe . Here, we show that S. pombe autophagy in response to glucose limitation relies on mitochondrial respiration and the electron transport chain (ETC), but, in contrast to S. cerevisiae, the AMP-activated protein kinase (AMPK) and DNA damage response pathway components do not modulate fission yeast autophagic flux under these conditions. In the presence of glucose, the cAMP-protein kinase A (PKA) signaling pathway constitutively represses S. pombe autophagy by downregulating the transcription factor Rst2, which promotes the expression of respiratory genes required for autophagy induction under limited glucose availability. Furthermore, the stress-activated protein kinase (SAPK) signaling pathway, and its central mitogen-activated protein kinase (MAPK) Sty1, positively modulate autophagy upon glucose limitation at the transcriptional level through its downstream effector Atf1 and by direct in vivo phosphorylation of Rst2 at S292. Thus, our data indicate that the signaling pathways that govern autophagy during glucose shortage or starvation have evolved differently in S. pombe and uncover the existence of sophisticated and multifaceted mechanisms that control this self-preservation and survival response.